Intelectuais, sociabilidades e modelos de educação no Rio Grande do Norte (1889 - 1930) - Vieira, Arthur Cássio de Oliveira (2021)
This research is insert in the field of History of Education, articulating elements of cultural and political history. We aims to identify the main intellectuals that acted in the educational field of Rio Grande do Norte during the First Republic (1889-1930), as well as their sociability networks in public offices and scientific institutions of the period. We also aims to understand the models of education designed by them and taken over by these institutions, namely, the Historical and Geographic Institute of Rio Grande do Norte (IHGRN), the Teaching League of Rio Grande do Norte (LERN) and the Association of Teachers from Rio Grande do Norte (APRN). We defend the thesis that the sociability network woven among intellectuals was fundamental for the foundation of scientific institutions and the consolidation of a discourse and a practice of a modern education. We investigated publications and magazines of these associations, official documents, minutes, reports, government messages, compendiums and conferences, through discourse analysis from a Foucauldian perspective, which understands discourse as an instrument of power. Analyzing biographies using the prosopographicmethod, we build a collective biography of the group and your acting, presenting trajectories that intersect from sociability. We understand these sociability structures according to the discussions of Jean-François Sirinelli. We also used his concept of intellectual creators and cultural mediators, in a perspective of dialogue with the idea of representation by Roger Chartier, analyzing spatial and discursive representations of the models of education defended by these subjects. We observe, therefore, that these structures were built from belonging to social and political groups, as well as to institutions and their publications in Rio Grande do Norte on First Republic. Notice that the group's sociability and discourses legitimize subjects, guide practices and direct social and political actions towards the consolidation of arepublican model of education, guided by civics, hygiene and pedagogical modernity.